THE EFFECT OF BLENDED LEARNING TOWARD MEMORY RETENTION RATES OF NEONATAL RESUSCITATION SKILLS AND STUDENT’S PERCEPTION - Veratiwi Veratiwi; Nanan Sekarwana; Ike Rostikawati Husen (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: Retention is a goal in the learning process. The objective of this study was to compare the memory retention rates of neonatal resuscitation skills between blended learning strategies and conventional ones and to analyze the correlation of students’ perception on the implementation of blended learning towards memory retention rates of neonatal resuscitation skills.Method: This was an analytical study using quasi-experimental design applying posttest-only non-equivalent group design. The subjects of this study were students of DIII Midwifery Program of Health Polytechnic Palembang. The research subjects were divided into two groups; 25 subjects in blended learning group and 25 subjects in conventional group. The hypotheses were tested using Kolmogorov-Smirnov, to analyze the differences of memory retention rates of resuscitation skills between the two groups of study, and Chi-square test, to see the correlation of students’ perception on the implementation of blended learning with memory retention rates of resuscitation skills.Result: The results of study showed that the memory retention rates of neonatal resuscitation skills between blended learning group and conventional group were not significantly different. In addition, there was no correlation of students’ perception on the implementation of blended learning toward the memory retention rates of resuscitation skill.Conclusion: From the findings of this study, it can be concluded that there was no difference in the memory retention rates of neonatal resuscitation skills between blended learning strategies and conventional ones and there was no effect of the students’ perception on the implementation of blended learning towards the memory retention rates of neonatal resuscitation skills.